Analysis of complications that occurred in the perioperative period, when using different modes of fluid therapy - Kursov, Sergii; Lyzohub, Kseniia; Lyzohub, Mykola (ScienceRise: Medical Science, 2017)
Aim: To realize the clinical analysis of post-surgical complications in patients, who received intraoperative infuse therapy by the method of the restrictive mode of fluid resuscitation and purposeful fluid therapy for providing the adequate and stable hemodynamics in perioperative period and also for preventing the complications development. Materials and methods: the study was realized in 176 patients, who underwent surgical interventions in orthopedic oncology. The restrictive mode of fluid resuscitation was applied in 88 cases, and in 88 ones – the purposeful fluid therapy. The central hemodynamics was studied by the method of Cubichek tetrapolar rheography, coagulogram indications, dieresis speed, blood serum creatinine, frequency of postoperative nausea and vomit and enteroparesis were studied. Research results: the frequency of coagulopathy observations at purposeful fluid therapy didn’t reliably exceed the frequency of coagulopathy in patients with the restrictive mode. Patients, who underwent purposeful fluid therapy demonstrated the decrease of dieresis speed, postoperative nausea and vomit and enteroparesis reliably more seldom. At providing purposeful fluid therapy, there was observed the more stable hemodynamics, whereas patients with the restrictive mode of resuscitation reliably more often needed for the additional hemodynamic correction, which needed the use of vasopressors in 67 % of cases and unplanned increase of infusion therapy volume in 36 % of cases. Conclusions: the risk of complications of GIT and kidneys decreases at using purposeful fluid therapy, and the more stable postoperative hemodynamics comparing with the restrictive mode is guaranteed